Dancing into modernity : Singapore’s cabaret girls, 1930s-1970s - Kee, Andrea Hwee Yee (2019)
Singapore’s cabaret girls have recently made their way back into mainstream media thanks to local best-selling author Adeline Foo’s book, which documents their lives and efforts in overcoming negative perceptions. This thesis offers a different perspective by examining how discourses of gender and modernity developed alongside changing political and social contexts and ultimately contributed to the cabaret girls’ rise and eventual decline. By using newspaper archives to explore the lives and representations of these women, this thesis will argue that between the 1930s and 1970s, there was a transition from plural gendered concepts of modernity to a narrowing after the late 1950s. From the 1930s to the late 1950s, ambivalence surrounding ideas of modern womanhood allowed cabaret girls to employ different strategies to acquire socio-economic mobility and challenge marginalising discourses. However, challenging marginalisation became more difficult from the late 1950s with the process of decolonisation and nation-building. A new singular “modernity” emerged and it no longer had space for the cabaret girl, the world she inhabited and the ideas about gender and modernity she represented. This thesis will also reveal the limitations of ideas about modernity and progress, and their implications for contemporary issues surrounding globalisation and migrant labour.